The X protein of the hepatitis B virus acts as a transcription factor when targeted to its responsive element. - Unger, T (1990)
The X protein of hepatitis B virus (HBV) stimulates transcription of a large number of viral enhancers. This protein augments the activity of the HBV enhancer through a specific cis element, termed X responsive element (XRE). Multimers of XRE exhibit enhancer activity which is further stimulated by X. XRE binds multiple cellular transcription factors one of which is the C/EBP. We have constructed the DB gene containing the DNA-binding domain of the C/EBP. This gene efficiently represses the enhancer activity of the XRE by competitive displacement of the XRE-binding factors. Under these conditions, X was found to have only a partially stimulatory effect on transcription, suggesting that the XRE-binding proteins are required for the activity of X. In contrast, an X-DB hybrid protein that binds to the XRE is a strong transcription factor and acts without additional XRE-binding proteins. Furthermore, studies of X mutants revealed that the carboxy-terminus of the protein is required for this activation. These data show that X directly stimulates the cellular transcription machinery, possibly by protein-protein interaction with the XRE-binding factors.